Washoff of cypermethrin residues from slabs of external building material surfaces using simulated rainfall. (16th December 2013) - Trask, Jennifer R.; Harbourt, Christopher M.; Miller, Paul; Cox, Megan; Jones, Russell; Hendley, Paul; Lam, Chung
Abstract The use of pesticides by homeowners or pest‐control operators in urban settings is common, yet contributions of washoff from these materials are not easily understood. In the present study, cypermethrin, formulated as Cynoff EC (emulsifiable concentrate) and Cynoff WP (wettable powder) insecticides, was applied at typical rates to 10 different building material surfaces to examine its washoff potential from each surface. Using an indoor rainfall simulator, a 1‐h rainfall event was generated and washoff samples were collected from 3 replicates of each surface type. Washoff was analyzed for cypermethrin using gas chromatography‐negative chemical ionization mass spectrometry. An analysis of variance for a split‐plot design was performed. Many building materials had similar water runoff masses, but asphalt resulted in significantly reduced average water runoff masses (73% less). The Cynoff WP formulation generally produced greater cypermethrin washoff than the Cynoff EC formulation. In addition, results for both the WP and EC formulations indicated that smoother surfaces such as vinyl and aluminum siding had higher washoff (1.0–14.1% mean percentage of applied mass). Cypermethrin washoff from rough absorptive surfaces like concrete and stucco was lower and ranged from 0.1 to 1.3% and from 0 to 0.2%, respectively, mean percentage of applied mass. Both building material surface and formulation play a significant role in cypermethrin washoff. Environ Toxicol Chem 2014;33:302–307. © 2013 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution, and reproduction in any medium, provided the original work is properly cited.